P1-S6.39 Can professional midwives interpret rapid syphilis tests accurately?. (10th July 2011) - Gutiérrez, M A Chiappe; Soto, K; Lopez-Torres, L; Cárcamo, C; Calderón, M I Valderrama; La Rosa, S; Mallma, P; Garcia, P; Peeling, R
Abstract : Background: Congenital syphilis produces miscarriage and severe complications in newborns. Rapid syphilis testing (RST, Syphilis 3.0 Bioline) was introduced in antenatal care and reproductive health services of 16 health centers at Ventanilla (Callao), Peru, aiming to improving access to syphilis screening and treatment in the first contact of pregnant women with professional midwives. We present the results of a quality control assessment evaluating internal (IQC) and external quality control (EQC) of such tests when performed by professional midwives. Methods: We developed quality controls panels consisting of the Dried Tube Specimen (DTS). Open label positive and a negative control DTS were distributed as IQC bimonthly to services performing RST, to evaluate the test performance under the service storage conditions. Additionally, closed label controls (EQC) were distributed biyearly to evaluate the performance of each professional midwife performing RST. The ECC panel was composed of a weak positive, an intermediate and a strong positive DTS, as well as a negative DTS. Midwives were trained in DTS reconstitution, as well as result interpretation and recording. Results: 28 DTS panels were distributed for IQC (16 to antenatal and 3 to emergency services), with 100% concordance. 119 DTS panels were distributed as EQC, with 100% concordance observed in most (95%) of midwifes evaluated. Six midwives read the weak positive DTS as negative (75% concordance). These six professionals were retrained in their health centers. IQC and EQC were well accepted by midwifes, giving them a sense of confidence with their performance with the test. Conclusion: Excellent IQC and EQC results were observed, with good acceptance of the evaluation by midwives.